Pengaruh Faktor Sosial, Gaya Hidup, Dan Karakteristik Produk Terhadap Keputusan Pembelian - Sangun Subarman, Putra; Dunan, Hendri (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Business development has been colored by various kinds of competition. One of them is the increasingly fierce business competition which results in changes in consumer behavior in making decisions to buy a product. Motorcycle manufacturers also provide new innovations on motorbikes to make consumers interested in buying and using motorbikes. Consumers are very careful in choosing motorcycle products, because the motorcycles they choose reflect social and lifestyle factors, and product characteristics. The purpose of this study was to determine the magnitude of the influence of social factors, lifestyle, product characteristics on purchasing decisions for N Max Motorcycles in Bandar Lampung. This type of research is an explanatory research, with a population of consumers who buy Yamaha N Max motorcycles in Bandar Lampung, with a sample of 96 people determined using the proportion formula. Techniques of data analysis using multiple linear regression. Based on the calculation results, social factors have a positive effect on purchasing decisions for N Max motorcycles in Bandar Lampung. Lifestyle has a positive effect on purchasing decisions for N Max motorcycles in Bandar Lampung. Product characteristics have a positive effect on purchasing decisions for N Max motorcycles in Bandar Lampung. Social factors, lifestyle and product characteristics have a positive effect on purchasing decisions for N Max motorcycles in Bandar Lampung. The results of this study can be input for several interested parties and be beneficial to the company. So that the company will continue to maintain the viability of the company if consumers are loyal to the products produced.